Estimating the shear force carried by walls in rough rectangular channels using a new approach based on the radial basis function method. Issue 3 (3rd July 2017) - Khozani, Zohreh Sheikh; Bonakdari, Hossein; Akhtari, Ali Akbar; Zaji, Amir Hossein
ABSTRACT: Maximum and average shear stress in rectangular channels can be estimated using the percentage of shear force carried by walls (%SFw ), which is a parameter obtained using semi-empirical methods. The radial basis function (RBF) and Modified Structure RBF (MS-RBF) models are employed in this study to estimate %SFw . The two types of models performed well but an MS-RBF model with correlation coefficient ( R 2 ) of .9596 indicated better function than the RBF model with R 2 of .9462. Moreover, sensitivity analyses of the parameters affecting %SFw were carried out based on two statistical parameters using the MS-RBF models. Fifteen MS-RBF models with different input combinations were investigated and the best model with the lowest error values was selected. Subsequently, this optimum model was compared with three linear regression equations presented for rough and smooth rectangular channels and two equations suggested by other researchers for smooth ducts. The MS-RBF model with R 2 of .9743 made the best %SFw predictions compared with the other equations.